2022
DOI: 10.3389/fmed.2022.921016
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta-Analysis of Perioperative Analgesic Effects of Different Interventions on Postoperative Pain After Arthroscopic Shoulder Surgery Based on Randomized Controlled Trials

Abstract: BackgroundShoulder arthroscopic surgery is a common surgical method used in orthopedics. However, severe postoperative pain can significantly limit the early joint movement of patients and adversely affect the impact of the surgery. At present, there is no consistent and effective analgesic scheme for the management of postoperative pain after arthroscopic surgery of the shoulder.PurposeThe aim of this study was to search for the most effective analgesic scheme to control pain in the perioperative period of ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…For the non-nerve block group, the analgesic effect of external medication at 12 hours after operation is the best, and the analgesic effect of oral medication at 24 hours and 48 hours after operation is signi cantly better than other intervention measures. 25 However, there are few studies observed on electro-acupuncture for perioperative analgesic in shoulder arthroscopic surgery. Previous study con rmed that percutaneous electrical stimulation of acupoints (Hegu LI4, Neiguan PC6) during perioperative period can improve postoperative analgesia of patients undergoing arthroscopic shoulder surgery, delay the time of the rst use of analgesia pump, and reduce the amount of postoperative analgesics and adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…For the non-nerve block group, the analgesic effect of external medication at 12 hours after operation is the best, and the analgesic effect of oral medication at 24 hours and 48 hours after operation is signi cantly better than other intervention measures. 25 However, there are few studies observed on electro-acupuncture for perioperative analgesic in shoulder arthroscopic surgery. Previous study con rmed that percutaneous electrical stimulation of acupoints (Hegu LI4, Neiguan PC6) during perioperative period can improve postoperative analgesia of patients undergoing arthroscopic shoulder surgery, delay the time of the rst use of analgesia pump, and reduce the amount of postoperative analgesics and adverse events.…”
Section: Discussionmentioning
confidence: 99%